Early experience of seven hepatocellular carcinoma cases treated with regorafenib. Issue 11 (11th October 2018) - Uchikawa, Shinsuke; Kawaoka, Tomokazu; Aikata, Hiroshi; Kodama, Kenichiro; Inagaki, Yuki; Hatooka, Masahiro; Morio, Kei; Nakahara, Takashi; Murakami, Eisuke; Hiramatsu, Akira; Tsuge, Masataka; Imamura, Michio; et al.
Key Clinical Message: Regorafenib became second‐line treatment for the patients with sorafenib refractory. In our study, two patients could not continue regorafenib for its adverse effects. It was suggested that appropriate use criteria of regorafenib should be observed and manage adverse effects earlier. Abstract : Regorafenib became second‐line treatment for the patients with sorafenib refractory. In our study, two patients could not continue regorafenib for its adverse effects. It was suggested that appropriate use criteria of regorafenib should be observed and manage adverse effects earlier.